Legal aspects and government policy in increasing the role of MSMEs in the Halal ecosystem - Hidayat, Yusup; Machmud, Aris; Zulhuda, Sonny; Suartini, Suartini (F1000 Research Ltd, 2025)
Indonesia currently could not make it to the top ten global halal due to some external and internal factors, although it is the largest Muslim country. In the external sector, the competition map is getting tougher, while internally, there are handicaps in the form of weak public awareness of competition. As a country with the largest Muslim population in the world, Indonesia can become one of the largest markets in the world. As indicated in the Global Islamic Economic Report (GIER), Indonesia is one of the top ten countries that control the Islamic economic market, yet it fails to dominate its Islamic market. Accordingly, the government needs to play a stronger role through regulatory policies to encourage the development of the Islamic economic ecosystem in Indonesia (halal value chain). The purpose of this study is to find out and analyze the existence of Micro, small, and medium enterprises (MSMEs) in Indonesia in the world’s market for Halal products and Services.